Constitutional and legal status of the President of the Republic of China - Dariya Kirillovna Molchanova, Olga Olegovna Bazina, Yuri Ivanovich Leibo, Tamara Olegovna Kuznetsova; Alekseevna Slavkina, Nataliya (Opción, 2019)
The purpose of this study is the analysis of the institution of the head of state “with Chinese specifics” with use of comparative-legal and sociological methods. As a result, there is a substantial difference between the presidential powers set in the first Constitution and those defined in the effective one. The following conclusions should be outlined among others: The head of state in the People's Republic of China is a sole authority;Political and state powers are transferred to the candidate prepared in advance;The procedure of the powers transfer from one generation to another starts at the congress.